Designing a glass nanoshell on barium titanium trioxide to suppress nanocrystal growth during sintering for fine-grain dielectric ceramics - Jia Yu; Qi Jiang; Qingchao Jia; Liangzhu Zhang; Wenchun Chiu; Huidan Zeng (Journal of Materiomics)
Barium titanate (BaTiO3, BT) is one of the key dielectric materials for multilayer ceramic capacitor (MLCC) industry. To meet the development trend of miniaturization and high capacity of MLCC, the sintered ceramic with nanosized grain is required. Herein, we demonstrate a controllable preparation of fine-grain BaTiO3 ceramic by using sol-gel glass encapsulation strategy to suppress the growth of nanocrystal during sintering. It is found that the BaTiO3 nanocrystal with average lateral particle size of 70 nm and 200 nm (BT70 and BT200) can be coated with Bi2O3-B2O3-SiO2 (BBS) glass shell to form core-shell structures. The fine crystal of barium titanate ceramics can be achieved under different encapsulation quantities and sintering temperature. However, BT70, with a larger specific surface area, higher reactivity, and lower crystallinity, was more prone to hydrolyze in the sol-gel process, leading to the formation of a new phase after sintering, Ba2TiSi2O8, which adversely affected both the sintering behavior and dielectric properties. On the other hand, BT200 exhibited lower possibility to hydrolyze in the sol-gel process, resulting in single-phase ceramics after sintering. When the BT200 coated with 5% (in mass) BBS was sintered at 1100 °C, a dense BaTiO3 ceramic were obtained, with dielectric constant of 1194.23 and loss of 0.0139 at room temperature and 1 kHz. Therefore, this work provides a robust strategy for suppressing the nanocrystal growth during sintering for MLCC applications.